2002
DOI: 10.1182/blood.v99.2.443
|View full text |Cite
|
Sign up to set email alerts
|

Real-time quantitation of minimal residual disease in inv(16)-positive acute myeloid leukemia may indicate risk for clinical relapse and may identify patients in a curable state

Abstract: The inv(16) cytogenetic subtype of acute myeloid leukemia (AML) has a relatively good prognosis. Many patients achieve complete remission (CR). The prognostic uncertainty of negative qualitative reverse transcription-polymerase chain reaction (RT-PCR) assays suggests the need to identify prognostically significant critical thresholds by real-time RT-PCR. A reliable and sensitive (10 ؊5 ) real-time RT-PCR assay was set up for the evaluation of relevant CBF␤-MYH11/ABL transcript ratios and was applied to the 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 30 publications
4
82
0
2
Order By: Relevance
“…Interestingly, a recent RQ-RT-PCR study on adults positive for CBFB/MYH11 [inv (16)] has shown that most of the patients (4/5) with more than 100 normalized CBFB/MHY11 copies after induction had a relapse, whereas patients below this level never relapse. 41 Similar results were reported from Buonamici et al 42 All four relapse patients of our study were randomized in different therapy trials. In three of them an increase of the AML1/ ETO fusion transcript became obvious 9 weeks (pt.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, a recent RQ-RT-PCR study on adults positive for CBFB/MYH11 [inv (16)] has shown that most of the patients (4/5) with more than 100 normalized CBFB/MHY11 copies after induction had a relapse, whereas patients below this level never relapse. 41 Similar results were reported from Buonamici et al 42 All four relapse patients of our study were randomized in different therapy trials. In three of them an increase of the AML1/ ETO fusion transcript became obvious 9 weeks (pt.…”
Section: Discussionsupporting
confidence: 79%
“…Quantitative RT-PCR studies using competitive PCR or RQ-PCR enabled monitoring of the decrease in CBFB-MYH11 FG transcripts during early phases of induction and consolidation therapies. 33,45,46,176,177 However, due to the low number of patients so far examined, it was not possible to define a kinetic or a cutoff level for predicting relapse. 178 …”
Section: Table 26mentioning
confidence: 99%
“…4 Such favorable results with conventional chemotherapy led some authors to consider that allo-BMT is not indicated to consolidate first CR in these patients, even when a suitable donor is available. 46,172,173 Nevertheless, the relapse rate is still high indicating that reliable methods to detect MRD during hematologic CR are needed in order to better adapt the intensity of postremission therapy to specific cohorts of patients. So far, the use of qualitative RT-PCR-based methods employed to detect CBFB-MYH11 FG transcripts did not allow consistent Table 25 Expression values of the PML-RARA FG transcript in NB-4 cell line and bcr1 patients at diagnosis (phase IV) Comparison of PML-RARA FG transcript expression between BM and PB at diagnosis using either ABL, B2M or GUS as CG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, molecular monitoring of minimal residual disease was shown to early identify patient groups at high risk of relapse and therefore provide a window for therapeutic intervention. [1][2][3] Monitoring of MRD is mostly based on quantitative PCR. Common targets include specific fusion transcripts, for example, AML1-ETO, CBFB-MYH11, PML-RARA, and MLL gene fusions.…”
Section: Introductionmentioning
confidence: 99%